Determinant of Share Price in Property and Real Estate Subsector Companies - Lulu Amalia Nusron (Pusat P2M Politeknik Negeri Batam, 2022)
This research aims to determine the influence of financial performance of property and real estate sub-sector companies on the company's share price. Researchers retested because the results of previous studies were likely inconsistent. In addition, property and real estate companies that are used as research objects can be used as indicators to analyze the economic health of a country. However, based on historical performance data, property and real estate share prices fluctuate. Researchers used secondary data on the financial statements of property and real estate subsector companies registered in IDX for the period 2015-2019. The number of registered population is 64 companies but this study used sampling techniques with purposive sampling method so that only 15 companies registered and produced 75 samples for classical assumption test, multiple linear regression test, F test, t test, and determination coefficient test. The results of this study showed that the Current Ratio variable affects the share price with a significance value of 0.025. Earning per Share affects the share price with a significance value of 0.000, and Total Asset Turnover has a significant influence with a value of 0.024 to the share price. All three are also simultaneously influential. Interestingly in this study, for the direction of the hypothetical variable Current Ratio is negative so as to be contrary to the proposed hypothesis. Based on these results, it can be said that the current ratio value is not certain to indicate that the company can adequately pay off debt and avoid liquidity problems.